Analisis Status Akreditasi Rumah Sakit terhadap Kepuasan Tenaga Kesehatan dan Kepuasan Pasien di Rumah Sakit Hikmah Masamba - Winda Ovi Puspitasari; Mustamin Mustamin; Julia Fitrianingsih; Jangga Jangga; Muhammad Tahir Malik (Syntax Corporation Indonesia, 2024)
This study aims to analyze the effect of accreditation status on the satisfaction of health workers and patients at Hikmah Masamba Hospital, which is required by the Law of the Republic of Indonesia No. 44 of 2009 concerning Hospitals to carry out accreditation every three years to improve the quality of service and patient safety. Using qualitative methods and phenomenological approaches, data were collected through interviews with 15 health workers and 6 patients. The results of the study showed that accreditation had a positive impact on the satisfaction of both groups. Healthcare workers stated that their improved facilities, work safety, and attention to performance have met expectations. Meanwhile, patients are satisfied with the quality of physical and non-physical facilities, controlled waiting times, the accuracy of doctors in conducting visits, and the friendliness and caution of health workers in providing services. From these results, it can be concluded that accreditation status plays a significant role in increasing the satisfaction of both health workers and patients at Hikmah Masamba Hospital.